1993
DOI: 10.1039/p29930000229
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 2,6-dinitroanisole with cyclohexylamine in toluene–octanol binary solvents. Further support for the ‘dimer nucleophile mechanism’ in aromatic nucleophilic substitution

Abstract: The reaction of 2,6-dinitroanisole with cyclohexylamine in toluene, octanol and toluene-octanol mixtures has been studied at several amine concentrations. The reactions in toluene and in octanoltoluene mixtures up to 30% octanol show a third-order kinetic dependence on [amine]. Although the reaction rates in toluene and octanol are very similar, addition of small amounts of octanol to the toluene solution diminishes the rate of reaction, reaching a minimum value at 30-50% octanol, after which the rate increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…In the reactions of 2,6-DNA with cyclohexylamine [B] D 0.264 M in toluene and in octanol at 35, 45 and 60°C, it was observed that at 35°C the reaction is slightly faster in toluene than in octanol, whereas at 45 and 60°C the inverse is observed 177 . These results show, once more, the difficulties of studying related reaction rates at a single temperature.…”
Section: F Catalysis By Methanolmentioning
confidence: 81%
See 3 more Smart Citations
“…In the reactions of 2,6-DNA with cyclohexylamine [B] D 0.264 M in toluene and in octanol at 35, 45 and 60°C, it was observed that at 35°C the reaction is slightly faster in toluene than in octanol, whereas at 45 and 60°C the inverse is observed 177 . These results show, once more, the difficulties of studying related reaction rates at a single temperature.…”
Section: F Catalysis By Methanolmentioning
confidence: 81%
“…Although this argument could be refuted by the observation of the 'dimer nucleophile' in other systems 10 , it was of interest to examine the effect of addition of a hydrogenbond donor(HBD) co-solvent different from methanol, to the reaction of a substrate where the nucleofuge is methoxide, such as the reaction of 2,6-DNA with cyclohexylamine in toluene octanol binary mixtures 177 . As regards octanol: (a) it would not compete with the product (methanol) in case of a reversible reaction; (b) its dipolarity Ł D 0.37 is between that of toluene and methanol 178 ; (c) its hydrogen-bond donor ability (˛D 0.30 179 is greater than that of toluene or cyclohexylamine (˛D 0 for both) but smaller than that of methanol (˛D 0.69 179 .…”
Section: F Catalysis By Methanolmentioning
confidence: 99%
See 2 more Smart Citations
“…These reactions generally show second [1][2][3][4][5] and third order [6][7][8][9][10][11][12] dependence on amine in dipolar and nonpolar solvents, respectively. Further in nonpolar solvents these reactions exhibit an inverse temperature effect [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%